Numerical Study of Reducer Modification with Adjuster Opening Variations on Turbine Lube Oil Pipe - Agus Aopik; Bambang Arip Dwiyantoro (JMES The International Journal of Mechanical Engineering and Sciences, 2023)
The success criteria of the power plant are represented by EAF (Equivalent Availability Factor) value. In 2021, one of the causes of the Forced Outage (FO) at Adipala Steam Power Plant was the failure of the main lube oil turbine pipe. The sudden contraction of the reducer resulted in the previous failure. Modifications were made to the reducer using a conical shape to reduce the number of welding processes and minimize the probability of failure. Therefore, a study on reducer modification needs to be carried out to study the impact of changing the shape of the reducer and changing the opening check valve on process parameters and flow in the main lube oil turbine pipe. The modification of the reducer was the main focus in this study. This research aims to analyze the pressure of turbine lube oil in the existing adjuster and the modified adjuster, using the Computational Fluid Dynamics technique with check valve adjuster variations (distance between the tip of the check valve and the inner wall of the reducer). The inlet boundary condition was defined by a pressure inlet of 285803.4 Pa. Outlet boundary condition was set by a mass flow of 65.72 kg/s. The curve surface was set as wall boundary conditions with a stationary wall, no-slip, and standard roughness model. The oil pressure in the modified adjuster increased compared to the oil pressure in the existing adjuster. The pressure on the oil flow was required to distribute oil to the turbine bearings. With the small increase in pressure after the modification, the turbine lube oil transfer improved. The pressure drop (ΔP) value that occurred in the conical-shaped modified adjuster was smaller than the pressure drop (ΔP) in the existing adjuster. This is because the resistance on the modified adjuster was less than the existing adjuster. The flow streamlines that formed backflow and vortex on the conical modified adjuster were less compared to the existing adjuster due to fewer obstacles in the conical modified adjuster.